The Hybrid Aesthetic Functional (HAF) Appliance: A Less Visible Proposal for Functional Orthodontics - Christos Livas (Case Reports in Dentistry)
In modern orthodontics, aesthetics appear to have a decisive influence on orthodontic appliance preferences and acceptability. This paper reports the early application of a newly emerged functional device with enhanced aesthetics in a Class II treatment. Patient perspectives and technical considerations are discussed along with recommendations for further design development. It can be assumed that the use of thermoplastic material-based appliances may meet both the therapeutic and aesthetic demands of young age groups.